The effect of the healthcare professional - hospital relationship on accepting new clinical IT: a modified technology acceptance model from a relational perspective - Esmaeilzadeh, Pouyan; Sambasivan, Murali; Samy, Naresh Kumar (IEEE, 2010)
Moving into 21st century brings us fundamental transformations thanks to the rapid change of Information Technology (IT). Nowadays IT plays an important role in all fields. Especially, the application of IT has become pervasive in the health sector. Many consider clinical IT as a strategic healthcare tool to improve health care delivery, efficiency of medical care and clinical decision-making in medical practice. But, new technologies that change the traditional practice patterns of healthcare professionals in hospitals can not be simply accepted by them. There is enough evidence to say that healthcare professionals are not willing to accept and use clinical IT that interferes with their day-to-day work activities. If healthcare professionals, as the key players in medical practice, do not use new clinical IT, all the effort, money and resources used for the implementation of the system are doomed to failure. Although utilization of clinical IT is a sign of successful implementation of the IT project, factors affecting the healthcare professionals' acceptance of clinical IT are still not fully identified. In this study (as a conceptual research), the possibility of extending TAM to incorporate the unique characteristic of healthcare professionals and healthcare professional-hospital relationship is discussed. The modified model has been developed to address the issues of IT adoption amongst healthcare professionals in a hospital setting.